Five-years management of an emerging parasite risk (Eustrongylides sp., Nematoda) in a fishery supply chain located on Trasimeno Lake (Italy). (June 2022) - Franceschini, Raffaella; Guardone, Lisa; Armani, Andrea; Ranucci, David; Roila, Rossana; Valiani, Andrea; Susini, Francesca; Branciari, Raffaella
Abstract: In the last few years, the widespread diffusion of potentially zoonotic parasitic nematodes of the genus Eustrongylides in the Trasimeno Lake, Central Italy, prompted Food Business Operators (FBOs) operating in the freshwater fish supply chain to define preventive measures to reduce or eliminate this new hazard from fishery products. The results of the self-checks for parasite risk management of a fishermen's cooperative over a five-year period (January 2016–April 2021) are presented. Nine freshwater commercial species, perch ( Perca fluviatilis ), largemouth black bass  (Micropterus salmoides ), big-scale sand smelt ( Atherina boyeri ), eel ( Anguilla anguilla ), black bullhead ( Ictalurus melas ), carp ( Cyprinus carpio ), tench ( Tinca tinca ), goldfish ( Carassius auratus ), and pumpkinseed sunfish ( Lepomis gibbosus ), differently processed (filleted, whole gutted or whole ungutted), were investigated . The presence of visible parasites was assessed by visual inspection during processing and recorded. Eustrongylides sp. were found in all species examined except for goldfish. Eustrongylides sp. occurrence was negligible in large mouth black bass, eel, carp, and tench, while increasing prevalence rates over the years were observed in fillets of perch <400 g (from 4.2% in 2016 to 68% in 2021), batches of sand smelt (<1%–40%) and pumpkinseed sunfish (6%–99%). Still low but slightly increasing prevalence rates were also observed for black bull head. The rising of the infection in perch, sand smelt, and pumpkinseed sunfish lead to a progressive implementation of preventive measures including the definition of a sampling plan for the visual inspection followed by trimming or removal of the parasites from the muscle or the application of a threshold value to define the marketability of fish batches. This is the first study describing an approach for the management of the emerging risk posed by nematodes of the genus Eustrongylides in a freshwater fishery supply chain. Besides providing an updated epidemiological scenario in Lake Trasimeno, where this parasite was described for the first time in Italy in 2015, it could support other FBOs in the implementation of preventive measures to safeguard consumers' health and trust. Highlights: Eustrongylides sp. nematodes are becoming widespread in the Trasimeno Lake, Italy (85). The local freshwater fishery supply chain is affected by Eustrongylides sp. (85). 5-years of self-checks for parasites of a fishermen's cooperative are presented (82). Nine commercial species differently processed were investigated (65). Prevalence in perch, sand smelt and pumpkinseed sunfish are noticeably increased (85).